Short history of just mentorship and support - Šimunović, Vladimir J. (Array, 2008)
Summary: Since its foundation in 1992, the Croatian Medical Journal (CMJ) has followed the strict standards of quality in the scientific publishing. However, the Journal has been aware that its specific position demands more than just following the already established rules. From the very beginning, the Journal declared an “author-helpful policy,” stating that “journal editors should have a major role in training authors in science communication, especially in smaller and developing scientific communities. Journal authors usually send scientifically acceptable but poorly prepared articles and it is a pity to lose valid data because of their poor presentation.” (1,2). In brief, the editors and editorial staff of the CMJ have been well aware that the skills of scientific reporting and publishing in our academic community are not developed and that valuable research results and valid data are being lost because of poor presentation. To be perfectly honest, ten years ago this statement looked like a nice promise, one of the many we in academic medicine learnt not to take too seriously